Quo vadis, Moldova? The role of social and political elites in the norm internalization process. Issue 3 (3rd April 2022) - Baltag, Dorina; Burmester, Isabell
ABSTRACT: This article aims to assess the role of local agency and the local socio-cultural context in the internalization of externally promoted political norms. When external norms are diffused to the domestic level, they are reinterpreted and adapted to the local normative context. Conceptualized as a dynamic process, norm internalization implies that norms undergo a modification in terms of law, discourse, and practice. To add to the scholarship that offers power-based explanations when discussing how EU political norms are embraced locally, we discuss the internalization of norms at the national level, taking into consideration local reactions and the (re)interpretation of external norms. To do so, this article scrutinizes the local dynamic of the internalization process by showing how local agency and the cultural match between external and internal norms plays a role. Following the constructivist study of norm diffusion, this research uncovers how Moldovan social and political elites use societal pressure dynamic and elite learning dynamic in the case of implementation of the anti-corruption norm. In addition, this article puts emphasis on the importance of cultural match for a norm to be internalized by discussing post-Sovietness in Moldova.